(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
Uzbekistan, situated at the crossroads of ancient trade routes in Central Asia, boasts a rich and diverse cultural heritage that reflects centuries of historical influence. This abstract explores Uzbekistan’s historical significance, focusing on its pivotal role along the Silk Road and its enduring architectural marvels, such as the iconic Registan Square in Samarkand and the Bukhara Historic Centre. The discussion also highlights Uzbekistan’s vibrant intangible heritage, including traditional crafts, music, and cuisine, which continue to shape the country’s identity. Furthermore, the abstract delves into modern initiatives aimed at preserving and promoting Uzbekistan’s cultural treasures, from heritage conservation projects to sustainable tourism efforts. Ultimately, Uzbekistan’s commitment to safeguarding its cultural legacy ensures that its profound historical narrative remains accessible and cherished on both a national and global scale.